«The New Great Game» in Central Asia: the USА role (International relations and international law Journal, 2016)
The purpose of this article is to examine the definitions in US policy, which is one of the key players in the «Great Game» in Central Asia. The article deals with the basic theory and practical aspects of the «Great Game.» A key component in the creation of the «Great Game» was the competition for Central Asia, as well as in the article data between any countries conducted this rivalry. The authors analyzes the new position, the current agenda of the United States in the «Great Game» and a number of reasons for such a high interest in Central Asia. If you look at history, it is revealed that the US policy in Central Asia have gone through several phases, which have their own characteristics. These in turn affect a number of objective and subjective factors. Estimations and comment on the Role and opinions of the United States in the «New Silk Road» which is carried out on a global level.
Keywords: Central Asia; the Great Game; the problem; the US policy; history; geopolitics